NEUROFIBROMATOSE DE LINGUA - RELATO DE CASO - Garcia Martins, R. H. [UNESP]; Celice Castilho, E. [UNESP]; Prata Caobianco, G. R. [UNESP]; Trevilatto, C. [UNESP]; Suzuki Yoshinaga, S. L. [UNESP] (My University, 1995)
Neurofibromatosis may involve any part of the body, including cervical-facial region and intra-oral structures. The authors present a case of neurofibromatosis involving the tongue. They emphasize the need of close follow up of the patients as those lesions often show a high rate of recurrence.
Neurofibromatosis of the tongue - Report of a case
Keywords: neurofibromatosis; tongue; case report; female; human; preschool child; tongue tumor